LEARNING STRATEGY AND INTERLANGUAGE ERRORS: A CASE STUDY OF INDONESIAN STUDENTS LEARNING ENGLISH AS A FOREIGN LANGUAGENGLISH - Darussalam, Hanif (Kajian Linguistik dan Sastra, 2013)
The current study describes learning strategies in relation to interlanguage errors. As it is commonly believed that interlanguage errors are the result of cognitive mechanism or learning strategy used by second language learners. This study specifically describes the learning strategies employed by Indonesian learners of English which result in interlanguage errors. The data are sentences containing errors taken from studentsâ compositions. The technique used to collect the data is documentation, and the data are analyzed qualitatively. The result indicates that there are three major types of learning strategy used by the learners, including: overgeneralization, first language transfer, and simplification. Of these, the dominant learning strategy is overgeneralization which implies that the students have relied their linguistic knowledge on the target language (English) rather than on that of their first language. English teachers should have positive attitude on interlanguage errors since errors are an inevitable process in foreign language learning. They must also provide appropriate training for the students so that they are aware the differences between English and Indonesian. Such understanding could help them minimize errors and hence they will be able to develop their interlanguage system.